The Presentation and Index of the Harput Shari’ah Register Dated 1658-1659 (A.H. 1069) - Eğitmen, Buket (Fırat University, 2019)
Kadı records are one of the most important archive sources in Ottoman history. Kadı has duties both juristical and municipal. They fulfilled all these tasks, also, recorded their decisions and the copies of documents sent from the center. This registers are called the Shariah records. These records contains the following topics: trade, debt registration, property lawsuits, inheritance tax, guardianship determination, grants, alimony, tax, theft, insult, murder, as well as the copies of documents such as ferman, berat, tezkire, letter. In this study, the introduction of shariah registry dated 1658-1659 (A.H. 1069), which is of great importance for the history of Harput, was made and the summaries of the documents included in the registry were extracted.

Kadı sicilleri, Osmanlı tarihinin en önemli arşiv kaynaklarından biridir. Kadının hem hukuki hemde beledi görevleri vardır. Kadılar bütün bu görevleri yerine getirir, verdikleri kararları kayıtlara geçirir, merkezden gönderilen belgelerin suretini defterlere kaydederlerdi. Bu defterlere şer’iyye sicili denir. Bu sicillerde alım-satım, borç tescilleri, mal davaları, miras taksimi, vasi tayini, hibe, nafaka, vergi, hırsızlık, hakaret, cinayet gibi konuları içeren kayıtların yanında; ferman, berat, tezkire, mektup gibi belgelerin suretlerinin kayları da yer almaktadır. Bu çalışmada, Harput tarihi için büyük önem arz eden 1658-1659 tarihli şer’iyye sicilinin tanıtımı ve belgelerinin özetleri üzerinde durulmuştur.
1658-1659 (H. 1069) TARİHLİ HARPUT ŞER‘İYYE SİCİLİNİN TANITIMI VE FİHRİSTİ